Competing models of the modern Islamic state: Wahhabi vs. Muslim Brotherhood ideologies - Affan, Mohammad (AUC Knowledge Fountain, 2014)
n the aftermath of the Arab Spring, with the success of the Political Islam movements to seize power in some countries, such as Egypt and Tunisia, the problematic of the Islamic state was raised and ignited serious conflict between Islamists and seculars. Nevertheless, another hidden conflict seems to begin simultaneously in the camp of the Islamists itself between the Wahhabism and the Muslim Brotherhood, the two major Sunni Islamic movements. Each of them calls for a different model of the Islamic state. The Wahhabi ideology adopts a traditional state model, based on traditional legitimacy, centralized hierarchical power, and patriarchal form of state-society relationship. In contrast, The Muslim Brotherhood took a more adaptive approach, blending modern Western political thought with the Islamic tradition. Therefore, the research question was: what are the differences between the Islamic state model in the Wahhabi ideology and the models adopted by the Muslim Brotherhood? And why these differences are perceived by the Wahhabi regime as dangerous and perverted doctrines? In conclusion, the Muslim Brotherhood’s theories of the Islamic state seem to be in stark contrast with the Wahhabi model, regarding: the constitutional order, the mode of legitimacy, the power structure and distribution, and the pattern of citizenship. Both Muslim Brotherhood versions: the democratic and the radical, represent a direct threat on the authoritarian conservative model of the Wahhabi ideology. Therefore, the fears of emergence of a new Sunni Islamic state model that may de-legitimize the Saudi regime are responsible for this negative Saudi stance from the Muslim Brotherhood ideology.